Threat intelligence in practice : a practical guide to threat intelligence from successful organizations - Liska, Allan (O'Reilly Media, 2018)
Many organizations are discovering that traditional security tools alone aren't enough to protect their networks. In this practical report, you'll explore threat intelligence, a method for collecting information on various forms of malicious cyber activity as a way to bolster your in-house measures. Author Allan Liska, security architect at Recorded Future, takes you through the threat intelligence cycle and explains what is required to put together an effective threat intelligence program for your company. Backed by case studies of several organizations that have successfully implemented these initiatives, this report explains that threat intelligence is actionable external information that, when correlated against internal data, can be used to detect or prevent an attack. You'll understand how threat intelligence enables you to stay abreast of current as well as future threats. Understand exactly what threat intelligence is, and how to correlate it to internal events Collect and apply threat intelligence, gain feedback, and incorporate feedback into your own threat intelligence cycle Examine tactical, operational, and strategic intelligence, and ensure that the right information gets to the right people Get practical examples from several organizations that have correctly implemented threat intelligence programs.